2020
DOI: 10.18203/2320-6012.ijrms20204948
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition based on mid upper arm circumference and dietary consumption pattern of Lodha tribal children of West Bengal, India

Abstract: Background: Wasting, a form of malnutrition is a major public health burden in developing countries including India. Since, food and diet diversity have direct impact on nutritional status of children. The aim of the study was to assess the dietary consumption pattern and malnutrition based on mid upper arm circumference (MUAC) of Lodha tribal children of Paschim Medinipur and Jhargram districts of West Bengal, India.Methods: A total of 1043 Lodha preschool children (1-5 years) was selected for the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…DDS and DSS were very low for these Children. This is very similar to a study on Lodha children of West Bengal [29]. Children did not use to consume any healthy drinks due to their affordability but they consumed cheap fast food and junk food available in the market which may lead them obese in the future.…”
Section: Discussionsupporting
confidence: 84%
“…DDS and DSS were very low for these Children. This is very similar to a study on Lodha children of West Bengal [29]. Children did not use to consume any healthy drinks due to their affordability but they consumed cheap fast food and junk food available in the market which may lead them obese in the future.…”
Section: Discussionsupporting
confidence: 84%
“…20 MUAC is a reasonable method to assess the nutritional status of adults and the measurement is simply obtained by using measuring tape. 21,22 It is also used as a screening tool in conditions like famine and refugee crises. 23,24 In Pakistan, it is used in Thar, Thal and Cholistan where famine is simple to occur.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the consumption of energy was low, for boys of 2-3 years (16.1%) and 4-5 years (11.9%), and girls of 2-3 yeas (19.2%) and 4-5 years (24.2%) as compared to RDA, similar to a study on Lodha tribe by Sabud et al . [ 7 ] which also shows low energy consumption where RDA for girls (1062 ± 85.4 Kcal) and boys (1055 ± 79.2 Kcal).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, consumption of protein was low for boys of 2-3 years (25.2%) and 4-5 years (20.2%) and girls of 2-3 yeas (28.1%) and 4-5 years (20.1%) as compared to RDA in accordance with a study on Lodha tribe by Sabud et al . [ 7 ] had a low consumption of protein (17.92 ± 3.5%) in girls, (18.08 ± 3.1%) in boys as compared to RDA. Also our study shows, low fat consumption for both boys and girls, similar picture is revealed by other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation